Pengembangan E-LKPD berbasis kontekstual dengan media liveworksheets materi bangun ruang sisi datar untuk meningkatkan motivasi dan hasil belajar peserta didik SMP kelas VIII - Anjany, Fadhlillah (Maliki Interdisciplinary Journal, 2024)
Contextual-based development of E-LKPD during the Covid-19 pandemic which utilized Liveworksheet media in mathematics learning flat sided building material with the aim of increasing student motivation at home and improving student learning outcomes even though learning can only be carried out online.